Methodological strategies to stimulate levels of phonological awareness in students of the educational institution "Estrellitas de María", Chiclayo 2016 - Carbajal Cornejo, Katherine (2017)
This article presents the results of the research related to the application of methodological strategies, whose objective was to demonstrate that its application stimulates levels of phonological awareness in 5 - year - old children of the Educational Institution N ° 014 Estrellitas de María José Leonardo Ortiz Chiclayo. The "LESIFO" test adapted by the author was used to make the diagnosis. This instrument evaluated the levels of phonological awareness such as: lexical awareness, syllabic awareness and phonemic awareness in which students were present and applied to a single study group. From the analysis and interpretation of the results of the pre-test it was evidenced that the boys and girls evaluated reached a level of low achievement; After identifying and prioritizing educational needs, the program of game-based methodological strategies was developed, validated, and applied to stimulate levels of phonological awareness called "We Play to Listen to Better Understanding." The evaluation of the post test showed significant progress in the children at each of the levels of phonological awareness assessed, reaching a very high level of achievement by verifying the effectiveness of the proposed methodological strategies program.